Delivery of dimethyloxalylglycine in calcined bone calcium scaffold to improve osteogenic differentiation and bone repair. (26th February 2021) - Weng, Tujun; Zhou, Liangliang; Yi, Lingxian; Zhang, Chunli; He, Ying; Wang, Tianqi; Ju, Yue; Xu, Ye; Li, Li
Abstract: As hypoxia plays a vital role in the angiogenic-osteogenic coupling, using proline hydroxylase inhibitors to manipulate hypoxia-inducible factors has become a strategy to improve the osteogenic properties of biomaterials. Dimethyloxallyl glycine (DMOG) is a 2-ketoglutarate analog, a small molecular compound that competes for 2-ketoglutaric acid to inhibit proline hydroxylase. In order to improve the osteogenic ability of calcined bone calcium (CBC), a new hypoxia-mimicking scaffold (DMOG/Collagen/CBC) was prepared by immersing it in the DMOG-Collagen solution, followed by freeze-drying. All coated CBC scaffolds retained the inherent natural porous architecture and showed excellent biocompatibility. A slow release of DMOG by the DMOG-loaded CBC scaffolds for up to one week was observed in in vitro experiments. Moreover, the DMOG/Collagen/CBC composite scaffold was found to significantly stimulate bone marrow stromal cells to express osteogenic and angiogenic genes in vitro . In addition, the osteogenic properties of three kinds of scaffolds, raw CBC, Collagen/CBC, and DMOG/Collagen/CBC, were evaluated by histology using the rabbit femoral condyle defect model. Histomorphometric analyses showed that the newly formed bone (BV/TV) in the DMOG/Collagen/CBC group was significantly higher than that of the Collagen/CBC group. However, immunostaining of CD31 and Runx2 expression between these two groups showed no significant difference at this time point. Our results indicate that DMOG-coated CBC can promote osteogenic differentiation and bone healing, and show potential for clinical application in bone tissue engineering.